Characterization of the massively separated wake behind a square cylinder by means of direct numerical simulation - Vinuesa, Ricardo; Schlatter, Philipp; Henningson, Dan S. (Springer Proceedings in Physics, 2016)
The massively separated wake behind a wall-mounted square cylinder is investigated by means of direct numerical simulation (DNS). The effect of inflow conditions is assessed by considering two different cases with matching momentum thickness Reynolds numbers Reθ ≃ 1000 at the location of the cylinder: one with a fully-turbulent boundary layer as inflow condition, and another one with a laminar boundary layer. The main simulation is performed by using the spectral element code Nek5000. While in the laminar-inflow simulation the horseshoe vortex forming around the cylinder can be observed in the instantaneous flow fields, this is not the case in the turbulent-inflow simulation. Besides, the streaks in the turbulent case become greatly attenuated on both sides of the obstacle. By analyzing the Reynolds shear stress uv, we show that this is due to the modulation of the horseshoe vortex by the turbulence from the incoming boundary layer.
CRIS-Team Scopus Importer:2023-03-21